2014
DOI: 10.7763/ijmo.2014.v4.409
|View full text |Cite
|
Sign up to set email alerts
|

Simplified Thermo-Mechanical Modeling of Friction Stir Welding with a Sequential FE Method

Abstract: Abstract-This paper presents a methodology for modeling the transient thermal and mechanical responses without computing the heat generated by friction or plastic deformation. The externally applied heat source accounts for the heat generated from tool movement. The novel heat source model includes two parts: surface heat flux at the shoulder-workpiece interface and nodal heat generation in the material that should have been displaced by the tool. The heat source algorithm is described through equations and fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…A 3 D modelling is developed for analyzing thermal history during friction stir welding by the help of ANSYS APDL and similar results were found as previous [10]. Figure 6 shows temperature distribution during welding.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…A 3 D modelling is developed for analyzing thermal history during friction stir welding by the help of ANSYS APDL and similar results were found as previous [10]. Figure 6 shows temperature distribution during welding.…”
Section: Resultsmentioning
confidence: 66%
“…If contact shear stress is less than the value of 0.577 σ y behaves as sticking condition. In this model temperature dependent friction coefficient is used which vary 0.3 to 0.01 [10]. Figure 3 shows the modified coulomb's law.…”
Section: Frictional Contact Behaviourmentioning
confidence: 99%
“…They showed that temperature distribution in the friction stir welding process is symmetrical along the weld line. Hongjun Li and Di Liu [3] worked on simplified thermo-mechanical modeling of friction stir welding with a sequential FE method. They presented a methodology for modeling the transient thermal and mechanical responses without computing the heat generated by friction or plastic deformation.…”
Section: Literature Reviewmentioning
confidence: 99%